Identifikasi Warna Adonan Kerupuk Labusiam Menggunakan Sensor Warna Berbasis IoT - Susanti, Roza; Alfitri, Nadia; Aidha, Zas Ressy; Hidayat, Anton; Rahmawati, Anisa (Elektron : Jurnal Ilmiah, 2023)
Chayote (Sechium edule) is a fruit vegetable with nutritional content, which rich in minerals and vitamins. In West Sumatra, precisely in Tanah Datar Regency, Salimpauang District, chayote has become a household product, not only is it processed into vegetables, but chayote is also processed into snacks such as chayote chips. The process of processing chayote is generally still carried out conventionally by the Salimpauang community. To overcome the problem of automatic and remote monitoring of equipment during dough mixing by applying the IoT method. This monitoring system integrated with IoT was created using a NodeMCU 8266 microcontroller device and a TCS3200 color sensor. The TCS3200 color sensor is used to monitor color changes in chayote dough. Apart from that, this sensor is also used to determine differences in the evenness of the dough color. The RGB color of the dough so that the average value for a smooth texture is R>53, G>92 and B>42.